2011
DOI: 10.1590/s0103-84782011000100023
|View full text |Cite
|
Sign up to set email alerts
|

Serum biochemistry profile determination for wild loggerhead sea turtles nesting in Campos dos Goytacazes, Rio de Janeiro, Brazil

Abstract: Sea turtles are threatened to the point of extinction. The major goal of rehabilitating sick individuals is to eventually reintroduce them back into their habitat. In this way, they contribute to species preservation, as well as maintaining

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 11 publications
5
16
2
Order By: Relevance
“…The mean sodium levels were 139.6 ± 3.5 mequiv/l; Table 1 ), similar to those in reports for nesting sea turtles ( Deem et al , 2006 , 2009 ; Goldberg et al , 2011 ; Honarvar et al , 2011 ). Mean potassium levels were also similar to those reported in the literature for nesting sea turtles ( Deem et al , 2006 , 2009 ; Honarvar et al , 2011 ).…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The mean sodium levels were 139.6 ± 3.5 mequiv/l; Table 1 ), similar to those in reports for nesting sea turtles ( Deem et al , 2006 , 2009 ; Goldberg et al , 2011 ; Honarvar et al , 2011 ). Mean potassium levels were also similar to those reported in the literature for nesting sea turtles ( Deem et al , 2006 , 2009 ; Honarvar et al , 2011 ).…”
Section: Discussionsupporting
confidence: 88%
“…To our knowledge, this is the first study in the literature to report on biochemical reference intervals for nesting hawksbills in the South Atlantic Ocean. The triglyceride concentrations (1033 ± 202 mg/dl; Table 1 ) were significantly higher than those found in other sea turtle species ( Hasbún et al , 1998 ; Goldberg et al , 2011 ). Cholesterol levels (287 ± 42 mg/dl) fall within the range found by Hasbún et al (1998) for female green turtles in the United Arab Emirates (226.08 ± 123.06 mg/dl) and by Goldberg et al (2011) for nesting loggerheads in Brazil (247.75 ± 48.52 mg/dl).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The survival rate of rehabilitated animals once released back into the wild could be lower than that of wild turtles, further reducing overall success rates in terms of the potential for individuals to contribute to the population (Cardona et al 2012). Widespread rehabilitation of sick or injured turtles currently supplements other conservation efforts (IUCN 1995, Casal & Orós 2009, Goldberg et al 2011, Mestre et al 2014), but we still have a poor understanding of the conservation potential of rehabilitation in terms of numbers of healthy animals released (even without knowing their longer-term individual survival; Cardona et al 2012, Mestre et al 2014.…”
Section: Introductionmentioning
confidence: 99%
“…McFadden et al (2014), found an average of 0.9 mg/dL (± 0.5), as well as Caliendo et al (2010) 1.7 mg/dL (±0.4), in this study, close values were found for hawksbill turtle 1.06 mg/dL (± 0.69). However, in loggerhead sea turtles, that have a different feed, mean uric acid values were found that ranged between 0.3 mg/dL and 1.2 mg/dL (mean 0.62 mg/dL ± 0.21) (GOLDBERG et al, 2011).…”
Section: Discussionmentioning
confidence: 96%